Newly Revealed Subterranean Structures Beneath Hagia Sophia’s Atrium - Diker, Hasan Fırat (Walter de Gruyter GmbH, 2026)
At the beginning of 2025, the cleaning of the subterranean structures of Hagia Sophia, initiated by the Directorate General of Foundations under the Ministry of Culture and Tourism of the Republic of Türkiye, resulted in highly significant discoveries. In its initial phase, the work commenced in the vaulted cellars forming the basement level of the now-nonexistent atrium of Hagia Sophia, as these spaces were relatively more acces- sible. As the cleaning process advanced, previously unknown subterranean structures were revelaed. Conducted under the supervision of archaeologists, this process has yielded remarkably valuable data concerning the multilayered and complex underground system beneath the atrium of Hagia Sophia. By evaluating and discussing the initial findings, this study is expected to contribute to the rich architectural history of Hagia Sophia. As the cleaning of its subterranean structures, carried out by the Directorate General of Foundations, progresses further, the infrastructural system of this unique world heritage monument will be revealed in its entirety.
Keywords: Hagia Sophia; Subterranean; Atrium; Vault; Tunnel